Mapping Publication Trends of Influencer Marketing and Digital Political Campaigns: A Bibliometric Analysis - Andi Visca Irfa Nyssa; Suswanta; Inrinofita Sari (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This paper aims to identify trends and map research on the role of influencer marketing in digital political campaigns, which has been a focus among academics and practitioners. The method used in this study is qualitative research with a literature review approach. The study found that influencer marketing has increased significantly between 2019 and 2023, successfully building credibility and reaching a wider audience on social media platforms. However, challenges include the spread of false information and the polarization of public opinion. The study concludes that influencer marketing can encourage voter participation and improve political literacy, but ethics and transparency are crucial to maintaining public trust. This research provides strategic insights for maximizing inclusive, data-driven digital political campaigns.